The impact of primary percutaneous coronary intervention strategies during ST-elevation myocardial infarction on the prevalence of coronary microvascular dysfunction - Ali Aldujeli; Ayman Haq; Tsung-Ying Tsai; Ingrida Grabauskyte; Vacis Tatarunas; Kasparas Briedis; Sumit Rana; Ramunas Unikas; Anas Hamadeh; Patrick W. Serruys; Emmanouil S. Brilakis (Scientific Reports, 2023)
Abstract Coronary microvascular dysfunction (CMD) is a common complication of ST-segment elevation myocardial infarction (STEMI) and can lead to adverse cardiovascular events. This is a non-randomized, observational, prospective study of STEMI patients with multivessel disease who underwent primary PCI, grouped based on whether they underwent balloon pre-dilatation stenting or direct stenting of the culprit lesion. Coronary physiology measurements were performed 3 months post-PCI including coronary flow reserve (CFR) and index of microcirculatory resistance (IMR) measurements at the culprit vessel. The primary endpoint was the prevalence of CMD at 3 months, defined as IMR ≥ 25 or CFR < 2.0 with a normal fractional flow reserve. Secondary endpoints included major adverse cardiovascular events (MACE) at 12 months. Two hundred ten patients were enrolled; most were men, 125 (59.5%), with a median age of 65 years. One hundred twelve (53.2%) underwent balloon pre-dilatation before stenting, and 98 (46.7%) underwent direct stenting. The prevalence of CMD at 3 months was lower in the direct stenting group than in the balloon pre-dilatation stenting group (12.24% vs. 40.18%; p < 0.001). Aspiration thrombectomy and administration of intracoronary glycoprotein IIb/IIIa inhibitors were associated with lower odds of CMD (OR = 0.175, p = 0.001 and OR = 0.113, p = 0.001, respectively). Notably, MACE in patients who underwent direct stenting was lower than in those who underwent balloon pre-dilatation before stenting (14.29% vs. 26.79%; p = 0.040). In STEMI patients with multivessel disease, direct stenting of the culprit lesion, aspiration thrombectomy and administration of intracoronary glycoprotein IIb/IIIa inhibitors were associated with a lower prevalence of CMD at 3 months and lower incidence of MACE at 12 months compared with balloon pre-dilatation stenting. This trial is registered at https://ichgcp.net/clinical-trials-registry/NCT05406297 .